Nonlinear relationship between Intellectual Property Protection (IPP) and renewable energy innovation (REI) in 27 countries - Luo, Heng; Zhang, Lianping; SUN, YING; Kamarudin, Fakarudin; Setyowati, Arum (Springer Nature, 2025)
In the pursuit of global sustainability, renewable energy innovation (REI) plays a pivotal role in mitigating climate change and reducing reliance on fossil fuels. However, the development of renewable energy technologies is fraught with significant challenges, such as high upfront capital costs and technical uncertainties. Intellectual Property Protection (IPP) emerges as a crucial mechanism in this context, promoting knowledge diffusion and incentivising innovation. This study investigates the nonlinear relationship between IPP and REI across 27 countries, which together account for over 90% of global REI, while also considering heterogeneity in resource rents and political stability. In addition, it explores the moderating role of urbanisation in this nonlinear nexus and investigates the threshold effect of financial development (FD). To achieve these objectives, this study employs a fixed effects model and a threshold effects model. Outcomes confirm the existence of an inverted U-shaped relationship. The heterogeneity analysis reveals that this nonlinear effect is present only in groups with above-average resource rent and political stability. Urbanisation strengthens the inverted U-shaped relationship, while FD serves as a threshold variable, with higher FD weakening the negative effects of IPP. Lastly, specific policy recommendations are proposed to enhance renewable energy innovation.